Ferdinand von Fürstenberg - Elit, Stefan (Frühe Neuzeit in Deutschland. 1620-1720. Literaturwissenschaftliches Verfasserlexikon (VL17), Bd. III)

Hartmann von Aue 1230–1517. Kulturgeschichtliche Perspektiven der handschriftlichen Überlieferung

Figuren des Dritten im höfischen Roman, Beiträge zur mediävistischen Erzählforschung 2020, Themenheft 4

Tragfähige Grundlagen - Häsel-Weide, Uta; Nührenbörger, Marcus (Kinder lernen Zukunft – Anforderungen und tragfähige Grundlagen)

Aufgaben für den inklusiven Mathematikunterricht - aus der Sicht von Lehrkräften. - Heckmann, Lara; Häsel-Weide, Uta (Beiträge zum Mathematikunterricht 2020)

Sachrechnen - Häsel-Weide, Uta (Didaktik des Unterrichts bei Lernschwierigkeiten: Ein Handbuch für Studium und Praxis)

Mathematik (Primarstufe) in der Lehrerinnen- und Lehrerbildung. Qualifizierung für das Lehren von Mathematik in der Grundschule. - Häsel-Weide, Uta (Handbuch Lehrerinnen- und Lehrerbildung)

„Zeit, Raum und Subjektivität bei Hartmann von Aue und Burkhard von Hohenfels“ - Egidi, Margreth (Raum und Zeit im Minnesang. Ansätze – Spielarten – Funktionen (Studien zur historischen Poetik 29))

„Figuren des Dritten im höfischen Roman. Einleitung“ - Egidi, Margreth (Figuren des Dritten im höfischen Roman, Beiträge zur mediävistischen Erzählforschung 2020, Themenheft 4)

Historisches Vergleichen: Vergleichsaufgaben in Lehrwerken des Gesellschaftslehre- und Geschichtsunterrichts der Sekundarstufe II. Eine Untersuchung von (Schüler*innen-)Lösungen zu einer Vergleichsaufgabe am Beispiel eines Darstellungstextes zur Industriellen Revolution, Bd. 7: Geschichtsdidaktische Studien - Günther, Katrin

Was leisten neu zugewanderte Schülerinnen und Schüler im Fachunterricht? Online verfügbar - Günther, Katrin; Knauff, Michaele; Niederhaus, Constanze; Runskat, Tanja

Drüding, Markus; Schlutow, Martin (2019): Vergleich(en) im Geschichtsunterricht (Kleine Reihe – Geschichte). Frankfurt a. M.: Wochenschau Verlag - Günther, Katrin (Zeitschrift für Geschichtsdidaktik (19))

Die nächste Generation der Grounded Theory: Situational Analysis nach Clarke und ihr Potenzial für die Fremdsprachenforschung - Ballweg, Sandra (Sprachen, Kulturen, Identitäten: Umbrüche durch Digitalisierung? Dokumentation zum 28. Kongress für Fremdsprachendidaktik der Deutschen Gesellschaft für Fremdsprachenforschung (DGFF) Würzburg, September 2019)

Portfolioarbeit - Ballweg, Sandra (Handbuch Methoden im Fremdsprachenunterricht)

Mehrsprachigkeit in der Familie: Einführung in den Themenschwerpunkt - Ballweg, Sandra (Zeitschrift für Interkulturellen Fremdsprachenunterricht)

Fachkulturen unter der Lupe: Metaphern in Reflexionen über die Lehre - Scharlau, Ingrid (die hochschullehre)
Metaphern spielen Ansätzen der Kognitiven Linguistik zufolge eine wichtige Rolle dafür, sich abstrakte Sachverhalte zu erschließen. Die Autorin analysiert zwei Interviews über Fachkulturen aus einer früheren Untersuchung (Scharlau und Huber 2019) auf ihre wichtigsten lehrbezogenen Metaphern. Diese werden auf der Basis von kognitiv-linguistischen Ansätzen und Methoden interpretiert und Ansätze für eine hochschuldidaktische Nutzung eines solchen Blickwinkels skizziert.
Keywords: Fachkultur; Fachkulturen; Metapher

Understanding and Explaining Digital Artefacts - the Role of a Duality (Accepted Paper - Digital Publication Follows) - Budde, Lea; Schulte, Carsten; Buhl, Heike M.; Muehling, Andreas (Seventh International Conference on Learning and Teaching in Computing and Engineeringe)
Keywords: ⛔ No DOI found

The effect of triphenyl phosphate inhibition on flame propagation over cast PMMA slabs - Trubachev, S.A.; Korobeinichev, O.P.; Karpov, A.I.; Shaklein, A.A.; Glaznev, R.K.; Gonchikzhapov, M.B.; Paletsky, A.A.; Tereshchenko, A.G.; Shmakov, A.G.; Bespalova, A.S.; Yuan, Hu; Xin, Wang; et al. (Proceedings of the Combustion Institute)
Keywords: Physical and Theoretical Chemistry; Mechanical Engineering; General Chemical Engineering

Interferenzen von Mündlichkeit und Schriftlichkeit in der Gegenwartsliteratur - Markewitz, Friedrich (Germanistik. Internationales Referatenorgan mit bibliographischen Hinweisen)

Genderspezifik in thüringischen Fürstinnenkorrespondenzen der Frühen Neuzeit - Markewitz, Friedrich; Wille, Manuel (Zeitschrift für Angewandte Linguistik)

Mehrfach annotierte Textkorpora. Strukturierte Speicherung und Abfrage - Markewitz, Friedrich (Journal für Medienlinguistik)

Interkulturelle Kommunikation im Betrieb - Markewitz, Friedrich (Zeitschrift für Angewandte Linguistik)

Zur Verwendung eines Konzepts von Innerlichkeit als funktionaler Teil einer Inszenierungsstrategie in den Aufzeichnungen Rudolf Höß. Eine texthermeneutische Betrachtung - Markewitz, Friedrich (Zeitschrift für Literaturwissenschaft und Linguistik)

Texthermeneutische Zugänge und Reflexionen zum Diskursraum des Gettos Litzmannstadt anhand der komplexen Großtextsorte Getto-Tageschronik - Markewitz, Friedrich (Sprachwissenschaft)

Business Intelligence & Analytics Cost Accounting: An Action Design Research Approach - Grytz, Raphael; Krohn-Grimberghe, Artus; Müller, Oliver (European Conference on Information Systems)
In order to sustain their competitive advantage, data driven organizations must continue investing in business intelligence and analytics (BI&A) while mitigating inherent cost increases. Research shows that examining outlays by individual BI&A artifact (e.g. reports, analytics) is necessary, but introduction in practice is cumbersome and adoption is slow. BI&A service-oriented cost allocation (BIASOCA) represents an improvement to this situation. This approach enables to render the BI&A cost pool accountable and improves cost transparency, which leads to a higher BI&A penetration of economically viable applications in organizations. Against this background, this paper aims at designing and implementing BIASOCA in a medium-sized company. To record organizational impact and increase customer acceptance, this study is carried out as action design research (ADR). Our findings indicate improvements in BI&A management from working with consumers to locate cost savings and drivers. After invoicing, consumers’ BI&A awareness increased, releasing resources while also making a better understanding of BIASOCA necessary. We detail how to implement BIASOCA in a real-life setting and the challenges attendant in so doing. Our research contributes to theory and practice with a set of design principles highlighting, besides the accuracy of cost accounting, the importance of collaboration, model comprehensibility and strategic alignment.

Macht - Markewitz, Friedrich (WSK Band 6 (Wörterbücher zur Sprach- und Kommunikationswissenschaft): Text- und Diskurslinguistik)

Ironie - Markewitz, Friedrich (WSK Band 6 (Wörterbücher zur Sprach- und Kommunikationswissenschaft): Text- und Diskurslinguistik)

Wissenschaftssprache - Markewitz, Friedrich (WSK Band 6 (Wörterbücher zur Sprach- und Kommunikationswissenschaft): Text- und Diskurslinguistik)

Machtanalyse - Markewitz, Friedrich (WSK Band 6 (Wörterbücher zur Sprach- und Kommunikationswissenschaft): Text- und Diskurslinguistik)

Widerstand - Markewitz, Friedrich (WSK Band 6 (Wörterbücher zur Sprach- und Kommunikationswissenschaft): Text- und Diskurslinguistik)

Genealogie - Markewitz, Friedrich (WSK Band 6 (Wörterbücher zur Sprach- und Kommunikationswissenschaft): Text- und Diskurslinguistik)

Gouvernementalität - Markewitz, Friedrich (WSK Band 6 (Wörterbücher zur Sprach- und Kommunikationswissenschaft): Text- und Diskurslinguistik)

Dispositiv - Markewitz, Friedrich (WSK Band 6 (Wörterbücher zur Sprach- und Kommunikationswissenschaft): Text- und Diskurslinguistik)

Archäologie - Markewitz, Friedrich (WSK Band 6 (Wörterbücher zur Sprach- und Kommunikationswissenschaft): Text- und Diskurslinguistik)

Fachtextsorte - Markewitz, Friedrich (Fachtextsorte)

Gebrauchstextsorte - Markewitz, Friedrich (WSK Band 6 (Wörterbücher zur Sprach- und Kommunikationswissenschaft): Text- und Diskurslinguistik)

Trade and economic development: global causality and development- and openness-related heterogeneity - Gries, Thomas; Redlin, Margarete (International Economics and Economic Policy)

Digitalisierung in der Lehrerbildung durch Communities of Practice. Konzeption, Governance und Qualitätsmanagement des ComeIn-Verbundvorhabens in Nordrhein-Westfalen - van Ackeren, Isabell; Buhl, Heike M.; Eickelmann, Birgit; Heinrich, Martin; Wolfswinkler, Günther (Bildung, Schule und Digitalisierung)

Intergenerational Value Similarity in Adulthood - Hoellger, Christian; Sommer, Sabrina; Albert, Isabelle; Buhl, Heike M. (Journal of Family Issues)
This investigation concentrates on value similarity between parents and their children during adulthood. The interplay between gender, age, relationship quality, and frequency of contact on value similarity was analyzed. A total of 600 adult German children (53.8% women) and their parents took part in a questionnaire study. Value orientation was measured with a short version of Schwartz’s Portrait Values Questionnaire, and relationship quality with the Network of Relationships Inventory (Furman & Buhrmeister, 1992).Value similarity was higher in mother–daughter dyads compared to mother–son dyads, but in the other dyads, no significant differences were found. Regarding relationship quality, verbal intimacy was not related to value similarity. Parental satisfaction was associated with value similarity in the father–child dyads. Satisfaction, as perceived by adult children, was linked to value similarity in mother–child and father–son dyads. Furthermore, the frequency of contact related to value similarity between mothers and sons.
Keywords: Adult child–parent dyads; value similarity; relationship quality; frequency of contact; parent-child-relationship

Urbane Kulturen und Räume intermedial. Zur Lesbarkeit der Stadt in interdisziplinärer Perspektive

On the experimental study of condensation in pillow plate heat exchangers - Buckmann, Felix; Kenig, Eugeny

Inverse piezoelectric material parameter characterization using a single disc-shaped specimen - Feldmann, Nadine; Schulze, Veronika; Claes, Leander; Jurgelucks, Benjamin; Walther, Andrea; Henning, Bernd (tm - Technisches Messen)
The increasingly simulation-driven design process of ultrasonic transducers requires several reliable parameters for the description of the material behaviour. Exact results can only be achieved when a single specimen is used in the identification process, which typically is prone to the problem of low sensitivities to certain material parameters and thus high uncertainties. Therefore, a custom electrode topology for increased sensitivity is proposed for a piezoceramic disc. The thereupon conducted measurements of the electric impedance can be used as a starting point for an inverse approach where an equivalent simulation model is used to identify fitting material parameters. An optimisation strategy based on a preliminary sensitivity analysis is presented that leads to a good agreement between measurement and simulation. Furthermore, the proposed measurement procedure is able to evaluate the quality of the simulation model. Hence, different frequency-dependent damping models are presented and evaluated.

Linear Algebra driven by Data Science - Schramm, Thomas; Gasser, Ingenuin; Schwenker, Sören; Seiler, Ruedi; Lohse, Alexander; Zobel, Kay
Dieses Lernangebot widmet sich der linearen Algebra als dem Teil der Mathematik, der neben der Optimierung und der Stochastik die Grundlage für praktisch alle Entwicklungen im Bereich Künstliche Intelligenz (KI) darstellt. Das Fach ist jedoch für Anfänger meist ungewohnt abstrakt und wird daher oft als besonders schwierig und unanschaulich empfunden. In diesem Kurs wird das Erlernen mathematischer Kenntnisse in linearer Algebra verknüpft mit dem aktuellen und faszinierenden Anwendungsfeld der künstlichen neuronalen Netze (KNN). Daraus ergeben sich in natürlicher Weise Anwendungsbeispiele, an denen die wesentlichen Konzepte der linearen Algebra erklärt werden können. Behandelte Themen sind: Der Vektorraum der reellen Zahlentupel, reelle Vektorräume allgemein Lineare Abbildungen Matrizen Koordinaten und darstellende Matrizen Lineare Gleichungssysteme, Gaußalgorithmus Determinante Ein Ausblick auf nichtlineare Techniken, die für neuronale Netzwerke relevant sind.

Generalised Symmetry in Network Dynamics - Nijholt, Eddie; Rink, Bob; Schwenker, Sören (DSWeb)

A new algorithm for computing idempotents of ℛ-trivial monoids - Nijholt, Eddie; Rink, Bob; Schwenker, Sören (Journal of Algebra and Its Applications)
The authors of Berg et al. [J. Algebra 348 (2011) 446–461] provide an algorithm for finding a complete system of primitive orthogonal idempotents for CM, where M is any finite R-trivial monoid. Their method relies on a technical result stating that R-trivial monoid are equivalent to so-called weakly ordered monoids. We provide an alternative algorithm, based only on the simple observation that an R-trivial monoid may be realized by upper triangular matrices. This approach is inspired by results in the field of coupled cell network dynamical systems, where L-trivial monoids (the opposite notion) correspond to so-called feed-forward networks. We first show that our algorithm works for ZM, after which we prove that it also works for RM where R is an arbitrary ring with a known complete system of primitive orthogonal idempotents. In particular, our algorithm works if R is any field. In this respect our result constitutes a considerable generalization of the results in Berg et al. [J. Algebra 348 (2011) 446–461]. Moreover, the system of idempotents for RM is obtained from the one our algorithm yields for ZM in a straightforward manner. In other words, for any finite R-trivial monoid M our algorithm only has to be performed for ZM, after which a system of idempotents follows for any ring with a given system of idempotents.
Keywords: Applied Mathematics; Algebra and Number Theory

Quiver Representations and Dimension Reduction in Dynamical Systems - Nijholt, Eddie; Rink, Bob W.; Schwenker, Sören (SIAM Journal on Applied Dynamical Systems)
Dynamical systems often admit geometric properties that must be taken into account when studying their behavior. We show that many such properties can be encoded by means of quiver representations. These properties include classical symmetry, hidden symmetry, and feedforward structure, as well as subnetwork and quotient relations in network dynamical systems. A quiver equivariant dynamical system consists of a collection of dynamical systems with maps between them that send solutions to solutions. We prove that such quiver structures are preserved under Lyapunov--Schmidt reduction, center manifold reduction, and normal form reduction.
Keywords: Modeling and Simulation; Analysis

A Characterization of the Finiteness of Perpetual Integrals of Levy Processes - Kolb, Martin; Savov, Mladen (Bernoulli)
We derive a criterium for the almost sure finiteness of perpetual integrals of L ́evy processes for a class of real functions including all continuous functions and for general one- dimensional L ́evy processes that drifts to plus infinity. This generalizes previous work of D ̈oring and Kyprianou, who considered L ́evy processes having a local time, leaving the general case as an open problem. It turns out, that the criterium in the general situation simplifies significantly in the situation, where the process has a local time, but we also demonstrate that in general our cri- terium can not be reduced. This answers an open problem posed in D ̈oring, L. and Kyprianou, A. (2015).
Keywords: L ́evy processes; Perpetual integrals; Potential measures

Wahrheit, Freiheit, Demokratie – Zum Umgang mit Hochwertausdrücken in rechtspopulistischen bzw. neurechten Argumentationen anhand des Blogs „Politically Incorrect“ - Markewitz, Friedrich (Türkisch-Deutsche Studien Jahrbuch 2019:Migration movements and right-wing populism after 2015)

Generalized transitivity: A systematic comparison of concepts with an application to preferences in the Babington Smith model - Haddenhorst, Björn; Hüllermeier, Eyke; Kolb, Martin (International Journal of Approximate Reasoning)
Reciprocal relations are binary relations Q with entries Q(i,j)∈[0,1], and such that Q(i,j)+Q(j,i)=1. Relations of this kind occur quite naturally in various domains, such as preference modeling and preference learning. For example, Q(i,j) could be the fraction of voters in a population who prefer candidate i to candidate j. In the literature, various attempts have been made at generalizing the notion of transitivity to reciprocal relations. In this paper, we compare three important frameworks of generalized transitivity: g-stochastic transitivity, T-transitivity, and cycle-transitivity. To this end, we introduce E-transitivity as an even more general notion. We also use this framework to extend an existing hierarchy of different types of transitivity. As an illustration, we study transitivity properties of probabilities of pairwise preferences, which are induced as marginals of an underlying probability distribution on rankings (strict total orders) of a set of alternatives. In particular, we analyze the interesting case of the so-called Babington Smith model, a parametric family of distributions of that kind.

Auswirkungen der Digitalisierung industrieller Arbeit auf die allgemeine und berufliche Bildung - Berisha-Gawlowski, Angelina; Caruso, Carina; Goller, Michael; Harteis, Christian (Digitalisierung und Berufsbildung 4.0 am Übergang Schule - Beruf)